Transnational communication as the future of international communication - Oniszczuk, Zbigniew (Political Preferences, 2017)
Processes of globalization, digitalization and convergence have radically transformed mass communication, opening new possibilities for communicating. These transformations have also shaped the traditional international communication, based on the model of transmission and domination of nation states. This caused a need for new approach to the meaning and issues of such communication, hence such expressions as: international communication or global communication appeared in Polish literature of Media studies. In the opinion of German researchers the most adequate term, which also reflects the essence of transformations in international communication is: transnational communication. This article aims to explain this term by identifying its denotation, fields and perspectives for studies and by outlining characteristic features of transnational communication. Key words: international communication, global communication, transnational communication, states and national communities